Ceramic composite coating structure with anti-wear and anti-pollution coking function
Patent Information
- Application Number
- CN202521749782.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-18
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2035-08-18
AI Technical Summary
[0006]有鉴于此,本实用新型提供具有防磨损和抗沾污结焦功能的陶瓷复合涂层结构,以解决或缓解现有技术中存在的技术问题,至少提供一种有益的选择
[0048]优异的防磨损性能
Smart Images

Figure CN224884177U_ABST
Abstract
Description
Technical Field
[0001] This utility model relates to the technical field of ceramic composite coating structure, specifically a ceramic composite coating structure with anti-wear and anti-fouling and coking functions. Background Technology
[0002] In many industrial sectors, such as power plant boilers, industrial boilers, and kilns in the power, petroleum, petrochemical, and metallurgical industries, the high-temperature radiant metal substrate heating surfaces and fire-facing surfaces, as well as equipment such as rubber cutting tools, all face severe working environment challenges. Problems such as high temperature, high-speed fluid erosion, corrosion from complex chemical media, and material adhesion make the equipment surfaces extremely prone to wear, contamination, and coking.
[0003] Wear and tear gradually depletes the surface material of equipment, reducing its precision and lifespan, and increasing maintenance costs and downtime. For example, in boiler pipes, particles carried by high-temperature flue gas erode and wear down the inner wall of the pipe, leading to thinning of the pipe wall and even safety hazards such as leaks.
[0004] The problem of fouling and coking is equally serious. In equipment such as heating furnaces, impurities produced by fuel combustion, unburned substances, and components from the heated materials can easily deposit and coke on the equipment surface. This not only affects the heat transfer efficiency of the equipment, leading to energy waste, but may also change the operating conditions of the equipment and cause equipment failure.
[0005] Currently, while various protective coatings are available on the market, they often fail to simultaneously provide both abrasion resistance and anti-fouling / coking properties. Some traditional coatings perform poorly in abrasion resistance, easily wearing through in a short time; while others, although offering some resistance to fouling, lack sufficient anti-coking performance under high temperatures and complex operating conditions, failing to meet the demands of industrial production for long-term stable equipment operation. Therefore, developing a coating structure that can effectively solve these problems is of significant practical importance. Utility Model Content
[0006] In view of this, the present invention provides a ceramic composite coating structure with anti-wear and anti-fouling and coking functions to solve or alleviate the technical problems existing in the prior art, and at least provides a beneficial option.
[0007] The technical solution of this utility model embodiment is implemented as follows: a ceramic composite coating structure with anti-wear and anti-fouling and coking functions includes a base layer, a transition layer, a ceramic functional layer and a surface modification layer. The base layer is tightly attached to the surface of the equipment substrate, the transition layer is located on the base layer, the ceramic functional layer covers the surface of the transition layer, and the surface modification layer is the outermost layer of the coating.
[0008] More preferably, the base layer and the substrate are firmly adhered to each other through the physical embedding and metallurgical bonding of metal alloy particles with the substrate surface during the thermal spraying process.
[0009] More preferably, the transition layer and the base layer are also coated using a plasma spraying process.
[0010] More preferably, the ceramic precursor solution prepared by the sol-gel method can fully penetrate into the pores and micro-defects on the surface of the transition layer between the ceramic functional layer and the transition layer.
[0011] More preferably, the solution coating method between the surface modification layer and the ceramic functional layer allows the composite solution of fluoropolymer and nano-titanium dioxide to be uniformly covered on the surface of the ceramic functional layer.
[0012] This utility model embodiment, due to the adoption of the above technical solution, has the following advantages: In this utility model
[0013] I. Excellent wear resistance
[0014] From a structural design perspective, the nickel-chromium alloy base provides a good toughness foundation, capable of absorbing some external impact energy and reducing damage to the entire coating structure. The metal-ceramic composite material of the transition layer, especially the high hardness of silicon carbide, further enhances the coating's wear resistance. Meanwhile, the yttrium-stabilized zirconium oxide in the ceramic functional layer possesses extremely high hardness, reaching 15-20 GPa, effectively resisting high-speed fluid erosion and particle wear. Furthermore, the addition of graphene improves the coating's strength and toughness, making it less prone to brittle fracture under wear forces, instead dissipating energy through deformation, thus significantly improving the coating's wear life. Tests show that, under the same wear test conditions, the wear life of the ceramic composite coating of this invention is 3-5 times that of a traditional single coating.
[0015] Excellent anti-fouling and anti-coking properties
[0016] The fluoropolymer in the surface modification layer has extremely low surface energy, typically reaching 20-25 mN / m. This results in water droplets, oil stains, and other substances having a contact angle greater than 120° on the coating surface, almost rolling in a spherical manner, making it difficult for them to adhere to the coating surface and effectively preventing material contamination. The photocatalytic activity of nano-titanium dioxide works under light conditions, decomposing organic pollutants adsorbed on the coating surface into small molecules such as carbon dioxide and water, preventing organic matter from polymerizing and coking at high temperatures. The self-lubricating properties of graphene in the ceramic functional layer also reduce the friction between the material and the coating surface, reducing the material's residence time on the surface and the possibility of adhesion. Through practical application tests, in equipment such as heating furnaces, the use of the coating of this invention significantly reduces the phenomenon of contamination and coking on the equipment surface, and extends the cleaning cycle of the equipment by 2-3 times.
[0017] II. Good thermal and chemical stability
[0018] All components of the entire coating structure exhibit excellent high-temperature resistance and chemical stability. Yttrium-stabilized zirconia can withstand temperatures up to 1400℃, maintaining its crystal structure and performance stability even under high-temperature conditions, without undergoing phase transformations that could degrade coating performance. Nickel-chromium alloys and silicon carbide also possess excellent high-temperature resistance, enabling normal operation under high-temperature conditions. Regarding chemical stability, the coating resists corrosion from various chemical media. For example, after immersion in highly corrosive solutions such as 37% hydrochloric acid, 70% sulfuric acid, and 30% strong alkali for 300 days, the coating shows no obvious signs of corrosion, ensuring long-term stable operation of the equipment in complex chemical environments.
[0019] Improve equipment lifespan and energy efficiency
[0020] Because the ceramic composite coating of this invention has excellent anti-wear and anti-fouling / coking properties, the equipment surface is effectively protected, reducing equipment failures and maintenance frequency caused by wear and coking, thereby greatly extending the service life of the equipment. Taking boiler pipes as an example, after using this coating, the pipe replacement cycle can be extended by 2-3 years. At the same time, the anti-fouling / coking function keeps the equipment surface clean, improves heat transfer efficiency, and reduces energy waste. Actual operation tests have shown that in equipment such as heating furnaces, the energy utilization efficiency can be improved by 10%-15% after using this coating, demonstrating significant economic and environmental benefits.
[0021] The above overview is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments, and features described above, further aspects, embodiments, and features of the present invention will become readily apparent from the accompanying drawings and the following detailed description. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a structural diagram of the present utility model;
[0024] Figure 2 This is another structural view of the entire utility model;
[0025] Figure 3 This is a front view of the entire utility model;
[0026] Figure 4 This is a side view of the entire utility model.
[0027] Reference numerals: 1. Substrate; 2. Base layer; 3. Transition layer; 4. Ceramic functional layer; 5. Surface finishing layer. Detailed Implementation
[0028] In the following description, only certain exemplary embodiments are briefly described. As those skilled in the art will recognize, the described embodiments can be modified in various ways without departing from the spirit or scope of this invention. Therefore, the drawings and description are considered exemplary in nature and not restrictive.
[0029] The embodiments of this utility model will now be described in detail with reference to the accompanying drawings.
[0030] Example
[0031] like Figures 1-4 As shown, this utility model embodiment provides a ceramic composite coating structure with anti-wear and anti-fouling and coking functions, including a base layer 2, a transition layer 3, a ceramic functional layer 4 and a surface modification layer 5. The base layer 2 is tightly attached to the surface of the equipment substrate 1, the transition layer 3 is located on the base layer 2, the ceramic functional layer 4 covers the surface of the transition layer 3, and the surface modification layer 5 is the outermost layer of the coating.
[0032] In one embodiment, the base layer 2 and the substrate 1 are firmly adhered to each other through the physical embedding and metallurgical bonding of metal alloy particles to the surface of the substrate 1 during the thermal spraying process.
[0033] In one embodiment, specifically, the transition layer 3 and the base layer 2 are also coated using a plasma spraying process.
[0034] In one embodiment, specifically, between the ceramic functional layer 4 and the transition layer 3, the ceramic precursor solution prepared by the sol-gel method can fully penetrate into the pores and micro-defects on the surface of the transition layer 3.
[0035] In one embodiment, specifically, between the surface modification layer 5 and the ceramic functional layer 4, a solution coating method is used to ensure that the composite solution of fluoropolymer and nano-titanium dioxide can be uniformly covered on the surface of the ceramic functional layer 4.
[0036] When this utility model is in operation: The coating structure consists of...
[0037] The ceramic composite coating structure consists of, from bottom to top, a base layer 2, a transition layer 3, a ceramic functional layer 4, and a surface finishing layer 5.
[0038] Base Layer 2: Base Layer 2 is in direct contact with the surface of the equipment substrate 1, and its function is to enhance the adhesion between the coating and the substrate 1. Base Layer 2 is made of a metal alloy material, such as a nickel-chromium alloy (e.g., Inconel 625), and is uniformly sprayed onto the surface of the substrate 1 using a thermal spraying process to form a base layer 2 with a thickness of 50-100 μm. Nickel-chromium alloys have good toughness and affinity with the substrate 1, enabling them to adhere firmly to the substrate 1 and provide a stable foundation for the subsequent coating construction.
[0039] Transition Layer 3: Located above the base layer 2, the transition layer 3 primarily alleviates stress concentration issues caused by differences in thermal expansion coefficients between the base layer 2 and the ceramic functional layer 4, thereby improving the overall stability of the coating. The transition layer 3 is made of a metal-ceramic composite material, such as a composite of silicon carbide (SiC) and nickel-chromium alloy. Plasma spraying technology is used to prepare the transition layer 3, controlling its thickness to 30-80 μm. Silicon carbide possesses high hardness and good wear resistance; when combined with nickel-chromium alloy, it can adapt to the different performance characteristics of the base layer 2 and the ceramic functional layer 4, further enhancing the wear resistance of the coating.
[0040] Ceramic functional layer 4: Ceramic functional layer 4 is the key component for the coating to achieve its anti-wear and anti-fouling / coking functions. This layer mainly consists of yttrium-stabilized zirconium oxide (YSZ), graphene, and a small amount of niobium oxide (Nb2O5). A ceramic functional layer 4 with a thickness of 80-150 μm is formed on the surface of transition layer 3 through a combination of sol-gel method and high-temperature sintering process. Yttrium-stabilized zirconium oxide possesses excellent high-temperature resistance, high hardness, and good chemical stability, effectively resisting wear and high-temperature corrosion. The addition of graphene significantly improves the strength and toughness of the coating, while its unique two-dimensional structure endows the coating with good self-lubricating properties, reducing the friction between the material and the coating surface, and reducing the possibility of contamination and coking. Niobium oxide plays a role in improving the microstructure and increasing the density of the coating.
[0041] Surface Modification Layer 5: Located on the outermost layer of the coating, surface modification layer 5 aims to further optimize the surface properties of the coating and enhance its resistance to fouling and coking. Surface modification layer 5 is a composite coating of fluoropolymer and nano-titanium dioxide (TiO). It is uniformly coated onto the surface of the ceramic functional layer 4 using a solution coating method, and after curing, forms a surface modification layer 5 with a thickness of 10-30 μm. The fluoropolymer has extremely low surface energy, making it difficult for water droplets, oil stains, and other substances to adhere to the coating surface, achieving a self-cleaning function. Nano-titanium dioxide not only has photocatalytic activity, decomposing organic pollutants under light conditions to further prevent coking, but also improves the weather resistance of the coating.
[0042] Connection methods between layers
[0043] The base layer 2 and the substrate 1 achieve a strong adhesion through the physical embedding and metallurgical bonding of metal alloy particles to the surface of the substrate 1 during the thermal spraying process. During thermal spraying, high-temperature metal alloy particles impact the surface of the substrate 1, and some particles embed into the micropores on the surface of the substrate 1. At the same time, they undergo a certain degree of diffusion reaction with the surface of the substrate 1, forming a metallurgical bond, thereby ensuring high adhesion between the base layer 2 and the substrate 1.
[0044] The transition layer 3 and the base layer 2 are also bonded using a plasma spraying process. During the spraying of the transition layer 3 material, the high-temperature metal-ceramic particles and the metal alloy particles on the surface of the base layer 2 fuse and diffuse with each other, forming a tight bonding interface. This bonding method allows the transition layer 3 to effectively alleviate the stress between the base layer 2 and the ceramic functional layer 4.
[0045] Between the ceramic functional layer 4 and the transition layer 3, the ceramic precursor solution prepared by the sol-gel method can fully penetrate into the pores and micro-defects on the surface of the transition layer 3. During the high-temperature sintering process, the ceramic precursor undergoes a chemical reaction to form ceramic crystals, which then form chemical bonds and mechanical interlocking with the metal-ceramic material on the surface of the transition layer 3, achieving a strong bond between the two.
[0046] Between the surface modification layer 5 and the ceramic functional layer 4, a solution coating method allows the composite solution of fluoropolymer and nano-titanium dioxide to uniformly cover the surface of the ceramic functional layer 4. During the curing process, van der Waals forces, hydrogen bonds, and other interactions are formed between the fluoropolymer molecules and the atoms or groups on the surface of the ceramic functional layer 4, thereby making the surface modification layer 5 firmly adhered to the ceramic functional layer 4.
[0047] Beneficial effects
[0048] Excellent wear resistance
[0049] From a structural design perspective, the nickel-chromium alloy of the base layer 2 provides a good toughness foundation, capable of absorbing some of the external impact energy and reducing damage to the entire coating structure. The metal-ceramic composite material of the transition layer 3, especially the high hardness of silicon carbide, further enhances the coating's resistance to wear. The yttrium-stabilized zirconium oxide in the ceramic functional layer 4 possesses extremely high hardness, reaching 15-20 GPa, effectively resisting high-speed fluid erosion and particle wear. Furthermore, the addition of graphene improves the coating's strength and toughness, making it less prone to brittle fracture under wear forces, instead dissipating energy through deformation, thus significantly improving the coating's wear life. Tests have shown that, under the same wear test conditions, the wear life of the ceramic composite coating of this invention is 3-5 times that of a traditional single coating.
[0050] Excellent anti-fouling and anti-coking properties
[0051] The fluoropolymer in surface modification layer 5 has extremely low surface energy, typically reaching 20-25 mN / m. This results in water droplets, oil stains, and other substances having a contact angle greater than 120° on the coating surface, almost rolling in a spherical manner, making it difficult for them to adhere to the coating surface and effectively preventing material contamination. The photocatalytic activity of nano-titanium dioxide works under light conditions, decomposing organic pollutants adsorbed on the coating surface into small molecules such as carbon dioxide and water, preventing organic matter from polymerizing and coking at high temperatures. The self-lubricating properties of graphene in ceramic functional layer 4 also reduce the friction between the material and the coating surface, reducing the material's residence time on the surface and the possibility of adhesion. Through practical application tests, in equipment such as heating furnaces, the use of the coating of this invention significantly reduces the phenomenon of contamination and coking on the equipment surface, and extends the cleaning cycle of the equipment by 2-3 times.
[0052] Good thermal and chemical stability
[0053] All components of the entire coating structure exhibit excellent high-temperature resistance and chemical stability. Yttrium-stabilized zirconia can withstand temperatures up to 1400℃, maintaining its crystal structure and performance stability even under high-temperature conditions, without undergoing phase transformations that would degrade coating performance. Nickel-chromium alloys and silicon carbide also possess excellent high-temperature resistance, enabling normal operation under high-temperature conditions. Regarding chemical stability, the coating resists corrosion from various chemical media. For example, after immersion in highly corrosive solutions such as 37% hydrochloric acid, 70% sulfuric acid, and 30% strong alkali for 300 days, the coating shows no obvious signs of corrosion, ensuring long-term stable operation of the equipment in complex chemical environments.
[0054] Improve equipment lifespan and energy efficiency
[0055] Because the ceramic composite coating of this invention has excellent anti-wear and anti-fouling / coking properties, the equipment surface is effectively protected, reducing equipment failures and maintenance frequency caused by wear and coking, thereby greatly extending the service life of the equipment. Taking boiler pipes as an example, after using this coating, the pipe replacement cycle can be extended by 2-3 years. At the same time, the anti-fouling / coking function keeps the equipment surface clean, improves heat transfer efficiency, and reduces energy waste. Actual operation tests have shown that in equipment such as heating furnaces, the energy utilization efficiency can be improved by 10%-15% after using this coating, demonstrating significant economic and environmental benefits.
[0056] Example 1
[0057] Base layer 2 preparation
[0058] Inconel 625 nickel-chromium alloy powder with a particle size of -150 to +50 μm was selected. Atmospheric plasma spraying equipment was used to heat the nickel-chromium alloy powder to a molten state and then spray it at high speed onto the surface of the equipment substrate 1, which had undergone sandblasting pretreatment. The plasma spraying process parameters were: main gas (argon) flow rate 60 L / min, powder delivery gas (nitrogen) flow rate 10 L / min, spraying current 800 A, spraying voltage 40 V, and distance between the spray gun and the surface of substrate 1 120 mm. Through the above process, a base layer 2 with a thickness of 70 μm was formed on the surface of the equipment substrate 1.
[0059] Preparation of transition layer 3
[0060] A composite powder of silicon carbide (SiC) and nickel-chromium alloy (Inconel 625) was prepared, wherein the SiC content was 40 wt% and the nickel-chromium alloy content was 60 wt%, and the powder particle size was -120 to +40 μm. The composite powder was then sprayed onto the surface of a base layer 2 using a plasma spraying process. The plasma spraying parameters were: main gas (argon) flow rate 70 L / min, powder feed gas (nitrogen) flow rate 12 L / min, spraying current 850 A, spraying voltage 42 V, and the distance between the spray gun and the surface of the base layer 2 was 130 mm. After spraying, a transition layer 3 with a thickness of 50 μm was formed.
[0061] Preparation of ceramic functional layer 4
[0062] First, a ceramic precursor solution was prepared. Appropriate amounts of zirconium oxychloride (ZrOCl2·8H2O) and yttrium oxide (Y2O3) were dissolved in ethanol to form a zirconium salt solution. Simultaneously, graphene was dispersed in an aqueous solution containing a dispersant and ultrasonically treated to achieve uniform dispersion. Then, an appropriate amount of niobium pentoxide (Nb2O5) powder was added to the above mixed solution, along with an appropriate amount of organic additive (such as citric acid). The mixed solution was stirred at 60°C for 2 hours to obtain a homogeneous ceramic precursor solution.
[0063] The prepared ceramic precursor solution was coated onto the surface of transition layer 3 using an impregnation-coating method, then dried at 120°C for 1 hour, and then placed in a high-temperature furnace to be heated to 1000°C at a heating rate of 5°C / min and held at that temperature for 2 hours for sintering. The above coating, drying and sintering process was repeated 3 times to finally form a ceramic functional layer 4 with a thickness of 100 μm.
[0064] Preparation of surface modification layer 5
[0065] A fluoropolymer (such as polytetrafluoroethylene, PTFE) is dissolved in an organic solvent (such as dichloromethane) to prepare a 10% (w / w) fluoropolymer solution. Simultaneously, nano-titanium dioxide (TiO2) powder (particle size 20-30 nm) is dispersed in an aqueous solution containing a dispersant and ultrasonically treated to achieve uniform dispersion. Then, the nano-titanium dioxide dispersion is slowly added to the fluoropolymer solution and stirred until homogeneous, yielding a composite solution of the fluoropolymer and nano-titanium dioxide.
[0066] The composite solution was uniformly coated onto the surface of the ceramic functional layer 4 using a spraying method. After drying naturally at room temperature for 1 hour, it was then cured at 80°C for 2 hours to form a surface modification layer 5 with a thickness of 15 μm.
[0067] Example 2
[0068] Base layer 2 preparation
[0069] The same Inconel 625 nickel-chromium alloy powder as in Example 1 was used, but the atmospheric plasma spraying process parameters were adjusted as follows: main gas (argon) flow rate 55 L / min, powder delivery gas (nitrogen) flow rate 9 L / min, spraying current 750 A, spraying voltage 38 V, and distance between the spray gun and the substrate 1 surface 110 mm. A base layer 2 with a thickness of 60 μm was formed on the surface of the equipment substrate 1.
[0070] Preparation of transition layer 3
[0071] A composite powder with a SiC content of 35 wt% and a nickel-chromium alloy content of 65 wt% was prepared, with a particle size of -130 ± 45 μm. The plasma spraying process parameters were adjusted as follows: main gas (argon) flow rate 65 L / min, powder feed gas (nitrogen) flow rate 11 L / min, spraying current 820 A, spraying voltage 41 V, and distance between the spray gun and the substrate surface 2 125 mm. A transition layer 3 with a thickness of 40 μm was formed.
[0072] Preparation of ceramic functional layer 4
[0073] The preparation method of the ceramic precursor solution is similar to that of Example 1, but the raw material ratio is adjusted. More graphene is added to the solution, increasing the mass fraction of graphene in the ceramic functional layer 4 from 3% in Example 1 to 5%. Simultaneously, the amounts of zirconium oxychloride, yttrium oxide, and niobium pentoxide are appropriately adjusted. The solution is coated onto the surface of the transition layer 3 using an impregnation-coating method. The drying and sintering process parameters are the same as in Example 1, but the coating, drying, and sintering processes are repeated four times to form a ceramic functional layer 4 with a thickness of 120 μm.
[0074] Preparation of surface modification layer 5
[0075] The mass fraction of the fluoropolymer solution was adjusted to 12%, and the particle size of the nano-titanium dioxide was selected to be 15-25 nm. The composite solution was uniformly coated onto the surface of the ceramic functional layer 4 using a brush coating method. After drying naturally at room temperature for 1.5 hours, it was cured at 90°C for 1.5 hours to form a surface modification layer 5 with a thickness of 20 μm.
[0076] Performance testing
[0077] Wear resistance test
[0078] Wear tests were conducted on the ceramic composite coatings prepared in Examples 1 and 2 using a pin-disc wear tester. The test conditions were: a load of 10 N, a rotation speed of 200 r / min, a wear time of 60 min, and SiC particles (particle size 100-150 μm) as the abrasive. After the test, the wear resistance of the coatings was evaluated by measuring the amount of wear. The results showed that the wear amount of the coating prepared in Example 1 was 0.025 g, and the wear amount of the coating prepared in Example 2 was 0.022 g, while the wear amount of a traditional single coating under the same test conditions was 0.08-0.12 g, indicating that the ceramic composite coating of the present invention has significant wear resistance advantages.
[0079] Anti-fouling and coking performance test
[0080] The coating samples prepared in Examples 1 and 2 were placed in an experimental apparatus simulating a heating furnace environment. High-temperature gas (800°C, gas flow rate 5 m / s) containing a certain amount of impurities and incompletely combusted substances was introduced for 100 hours. After the experiment, the contamination and coking conditions on the coating surface were observed. The results showed that the coatings prepared in Examples 1 and 2 had only a few slight contamination marks on their surfaces, with almost no coking. In contrast, the surfaces of the samples without the coating of this invention were covered with a thick layer of dirt and coking, demonstrating the excellent anti-contamination and coking function of the coating of this invention.
[0081] Thermal stability test
[0082] The coated samples were placed in a high-temperature furnace and heated from room temperature to 1200°C at a rate of 10°C / min, and held at that temperature for 5 hours. They were then cooled to room temperature with the furnace. This heating-cooling process was repeated five times, and the coating surface was observed for cracking, peeling, or other defects. Testing showed that the coatings prepared in Examples 1 and 2 remained intact during thermal cycling without significant defects, indicating good thermal stability.
[0083] Chemical stability test
[0084] The coated samples were immersed in 37% hydrochloric acid, 70% sulfuric acid, and 30% strong alkali solutions for 300 days, respectively. Samples were removed every 30 days to observe the corrosion on the coating surface and measure the thickness change. The test results showed no obvious signs of corrosion on the coating surface throughout the immersion process, and the thickness change was less than 0.01 mm, demonstrating the excellent chemical stability of the coating.
[0085] The above description is merely a specific embodiment of this utility model, but the protection scope of this utility model is not limited thereto. Any person skilled in the art can easily conceive of various variations or substitutions within the technical scope disclosed in this utility model, and these should all be included within the protection scope of this utility model. Therefore, the protection scope of this utility model should be determined by the protection scope of the claims.
Claims
1. A ceramic composite coating structure with anti-wear and anti-fouling / coking functions, characterized in that: It includes a base layer (2), a transition layer (3), a ceramic functional layer (4) and a surface finishing layer (5). The base layer (2) is tightly attached to the surface of the equipment substrate (1). The transition layer (3) is located on the base layer (2). The ceramic functional layer (4) covers the surface of the transition layer (3). The surface finishing layer (5) is the outermost layer of the coating.
2. The ceramic composite coating structure with anti-wear and anti-fouling / coking functions according to claim 1, characterized in that: The base layer (2) and the substrate (1) are firmly attached to each other through the physical embedding and metallurgical bonding of metal alloy particles to the surface of the substrate (1) during the thermal spraying process.
3. The ceramic composite coating structure with anti-wear and anti-fouling / coking functions according to claim 1, characterized in that: The transition layer (3) and the base layer (2) are also coated using a plasma spraying process.
4. The ceramic composite coating structure with anti-wear and anti-fouling / coking functions according to claim 1, characterized in that: Between the ceramic functional layer (4) and the transition layer (3), the ceramic precursor solution prepared by the sol-gel method can fully penetrate into the pores and micro-defects on the surface of the transition layer (3).
5. The ceramic composite coating structure with anti-wear and anti-fouling / coking functions according to claim 1, characterized in that: Between the surface modification layer (5) and the ceramic functional layer (4), the solution coating method enables the composite solution of fluoropolymer and nano titanium dioxide to be uniformly covered on the surface of the ceramic functional layer (4).